2015
DOI: 10.1007/978-94-017-7342-3_39
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Warm Mix Chemical Additives on the Binder-Aggregate Bond Strength and High-Service Temperature Performance of Asphalt Mixes Containing Electric Arc Furnace Steel Slag

Abstract: Warm Mix Asphalt (WMA) is a modified asphalt concrete, obtained by using organic, chemical or foaming additives, which can be produced and compacted at lower temperatures (100-140°C). The environmental sustainability of WMA can be enhanced with the inclusion of steel slag in substitution of natural aggregates. Given this background, this paper illustrates an experimental research aimed at characterizing WMA containing steel slag. Rheological tests were carried out on asphalt binders in order to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Hesami et al (2014) in a complete study on bituminous mixes with slag aggregates and their moisture susceptibility, demonstrated that slag used as sand degraded the water sensitivity. Similar results were found by Pasetto et al (2016). Conversely, the moisture resistance of coarse aggregate slag mixtures was very high (Ameri et al, 2013;Hesami et al, 2014).…”
Section: Moisture Sensitivitysupporting
confidence: 85%
“…Hesami et al (2014) in a complete study on bituminous mixes with slag aggregates and their moisture susceptibility, demonstrated that slag used as sand degraded the water sensitivity. Similar results were found by Pasetto et al (2016). Conversely, the moisture resistance of coarse aggregate slag mixtures was very high (Ameri et al, 2013;Hesami et al, 2014).…”
Section: Moisture Sensitivitysupporting
confidence: 85%
“…The influence of the warm additive on the nonrecoverable creep compliance seems negligible for all binders and mastics (except for the positive effect in the case of mastics containing steel slag at lower test temperature) suggesting that, according to previous research findings [7,8,33], such additive should not compromise rutting resistance with respect to the corresponding traditional hot material. On the other hand, the stiffening effect due to the addition of fillers, leading to the reduction of the rutting potential of mixtures, is clearly demonstrated by the sensibly reduced nr at all test temperatures with respect to the corresponding bitumens.…”
Section: High Service Temperature Behaviourmentioning
confidence: 59%
“…An additive dosage of 0.5% by weight of binder was selected to obtain the warm binder as recommended by the producer and according to the study on mixtures [33]. The warm binder was produced in the laboratory using a portable mixer operating at high stirring rates blending the prefixed amount of liquid additive and the hot plain binder (150 ∘ C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the replacement of virgin and recycled aggregates with steel slag is gaining momentum and strength as a way to improve some thermal and mechanical properties further (e.g., cohesion strength, stiffness, dynamic modulus, fatigue, and rutting) [56][57][58][59][60], likely due to its excellent roughness, shape, angularity, hardness, morphological, physical, polishing, and wear resistance [53]. Nonetheless, the results reported by other researchers are less conclusive, in the sense that steel slag mixtures exhibited lower mechanical performance (e.g., rutting performance) [58,61] and higher binder consumption [58,62] caused by the aggregate particle size and aggregate-type [63]. Therefore, many of the studies found in the literature review have focused on the heating and healing of mixtures containing only virgin (i.e., aggregates or fresh bitumen) and steel slag aggregates.…”
Section: Introductionmentioning
confidence: 99%